Effects of Chemical Treatments (Iron, Zinc and Salicylic Acid) and Soil Water Potential on Steviol Glycosides of Stevia (Stevia rebaudiana Bertoni.) - Ali Reza Gorzi; Heshmat Omidi; Amir Bostani (Iranian Journal of Chemistry & Chemical Engineering, 2020)
The most important characteristic of stevia is its high sweetness with zero calories which is due to the presence of Steviol glycosides (SVglys). This research aims to address the effect of salicylic acid (SA) and microelements viz. iron (Fe) and zinc (Zn) under different soil water potentials (-0.5, -3.5, -6.5 and -10 atm) on the production of SVglys and total sugar content in the leaves of stevia. The obtained results indicated that the soil water content and the exogenous application of SA and microelements significantly changed the accumulation of these sweet chemicals in the stevia leaves. The highest values of Stevioside (Stev), Rebaudioside C (Reb C), total SVglys and SVglys yield were obtained in SA + Fe + Zn treatment under the potential of -3.5 atm (76. 82, 2.82, 116.71 mg/g DW and 0.836 mg/g plant, respectively). Also, the HPLC results indicated that the highest rates of Rebaudioside A (Reb A) and the Reb A/Stev ratio (sweetness quality) belonged to SA + Zn treatment under the potential of -3.5 atm (28.63mg g-1 DW and 0.433). The application of SA + Fe + Zn was the most effective in terms of Rebaudioside B (Reb B), Dulcoside A (Dulc A), and total sugar (2.31, 5.73 and 335.8 mg/g DW, respectively). In general, our results suggest that it can be possible to improve the rate of secondary metabolites (SVglys) and hence the sweetness property in stevia leaves by applying SA, Fe, and Zn and particularly by the integrated application of these three agents.